Effects on nitrate leaching of the timing of cattle slurry application to leys. (20th May 2020) - Delin, Sofia; Stenberg, Maria
Abstract: This study compared the effects on nitrate leaching of slurry application to ley in early autumn (15 September), late autumn (1 November) and spring (April) under Swedish growing conditions. In two separate two‐year experiments, started in autumn 2009 and 2010, on a sandy loam soil in south‐west Sweden, these three application times were compared with no slurry application in grass–clover and grass swards. Soil water was sampled with ceramic suction cups, and nitrate leaching was calculated from water nitrate concentrations and drain discharge. Plant measurements indicated that, during autumn, the grass took up at least 20 kg of the 50 kg nitrogen (N) applied with slurry in September. The mineral nitrogen level in the subsoil (30–90 cm) in December was around 2 kg N ha −1 higher in this treatment. Nitrate leaching was on average 5 and 6 kg N ha −1 year −1 higher after early and late autumn slurry application, respectively, than after spring application ( p < .001), but the difference varied from 0 to 10 kg N ha −1 year −1 between experiments and sward types. Nitrate leaching losses in kg N ha −1 were lower from the grass sward, but higher if related to nitrogen inputs and dry matter yield. These results indicate that autumn application can increase the risk of nitrate leaching, but that early/late application within autumn is less important. It is more important to limit the amount of slurry applied in autumn and to consider other risks of nitrogen losses associated with time of application, such as ammonia emissions.